Estudo das inferências segundo a perspectiva pragmática de Grice, Sperber & Wilson e Levinson : uma abordagem comparativa - Rosa, Pamella Soares (2018)
The Pragmatics, a sub-area of Linguistics which integrates this work, studies the language in use, devoting itself to the understanding of the real meaning, including concepts such as inferences, context and subjectivity. The work developed here is a bibliographical one, constructed in such a way as to form a consistent theoretical basis on the generalized conversational inferences, in order to present a meta- analysis of selected articles involving these inferences and theories presented. The general objective of this dissertation is to compare the post and Neo-Gricean approach of cases of inferences, focusing on generalized conversational implicatures, in selected experiments, with specific objectives to understand the histories and philosophical bases related to Pragmatics, to discuss concepts relevant to the Gricean theory (Grice, 1957/1975), Post-Gricean (Sperber & Wilson, 1995) and Neo-Gricean (Levinson, 2000), observe the properties of inferences in theories and analyze pragmatic experiments concerning generalized conversational implicatures in order to understand how the inference process occurs in communicative practice and how the interpretation of generalized implicatures in human communication occurs. This proposal was developed due to the need for studies concerning the process of inferentiation, in order to contribute to an improvement of the study of communication through the understanding of the inferential process. The study made possible the understanding of how the neo and post-gricean theories describe the communication and the way in which this description is applied in the communicative dialogues. In addition, it was possible to observe the importance of understanding the historical and philosophical bases, allowing a delineation of the description and the pragmatic objects developed in this work, recognizing the proximity in the semantic-pragmatic relations, highlighting the standard implicatures of Levinson (2000) as responsible for importance of this approach for the understanding of the levels of meaning, verifying how the Neo and Post-Gricean theories occur with regard to generalized conversational inferences by means of a comparison between these pragmatic perspectives and the projection of the theory that best corresponds to the communicative practice to this type of implicature, advancing in the understanding of how the process of implication of the generalized implicatures occurs, understanding that, although the post-gricean approach better predicts the interpretation of this type of implicature, it is necessary to recognize the importance of Neo-Griceans of the scalar implicatures from lexical scales.